GROWTH AND PROPERTIES OF Cu2ZnSnS4 SINGLE CRYSTALS - I. V. Bodnar; I. A. Victorov; L. V. Volkova; S. A. Pauliukavets (Doklady Belorusskogo gosudarstvennogo universiteta informatiki i radioèlektroniki, 2019)
Polycrystalline ingots bridgman grown and by chemical method reactions of gas-transport connections Cu2ZnSnS4 single crystals of different forms: needle-like, plate and prismatic are received. The composition, structure of the grown single crystals was determined and unit cell parameters were calculated. The melt temperature was determined using DTA method. Transmission spectra in the region of intrinsic absorption edge were studied in temperature interval 20-300 K. The band gap width of Cu2ZnSnS4 single crystals was determined, its temperature dependency has been built and the calculation of the indicated dependency has been carried out. It was shown, that the experimental and calculated values are in good correlations.